LABORATORY FINDINGS OF CHILDREN ASSESSED IN RELATION TO COGNITIVE STATE BY THE HEALTH COMMITTEE OF A SECOND LEVEL STATE HOSPITAL - Fatma Gül Demirkan; Şeyma Karatekin (İstanbul Tıp Fakültesi Dergisi)
Objective: The aim of this study is to investigate the relation between anemia, vitamin deficiency, thyroid dysfunction, and the cognitive status of patients admitted to the medical board due to symptoms of cognitive retardation, a condition that is common in childhood and affects school success negatively. Materials and Methods: In this study, between January 2016- June 2018, serum vitamin B12, ferritin, hemogram and thyroid function tests of 71 pediatric patients, who were found to have had cognitive deficiencies and were admitted to the secondary level state hospital to obtain a medical committee report, were assessed retrospectively. Results: Among 71 children included in the study, 35.2% (n=25) were female and 64.8% (n=46) were male. Mean age was 11.5±2.1. Iron deficiency was detected in 9% of them. While 53.5% of them had normal vitamin B12 levels, the remaining had various degrees of vitamin B12 deficiencies. Thyroid dysfunction was not detected in any patient. There was no significant difference in vitamin B12 (p=0.2) and ferritin (p=0.6) levels in both genders. Normal intelligence score was obtained in 16 (22.5%) of all cases. Mild mental retardation was detected in 8 of the patients with vitamin B12 deficiency, borderline cognitive dysfunction was detected in 19 patients and cognitive dysfunction scores in 6 patients. While 10 of 38 patients without deficiency had normal intelligence quotient scores, 28 had at least 1 level of mental retardation. When the intelligence quotient of the patients with vitamin B12 deficiency and those with normal serum vitamin B12 were compared, no significant difference was found (p=0.13). There was no significant difference in vitamin B12 and ferritin levels when comparing patients with at least one level of mental retardation and normal intelligence scores (p=0.2; p=0.9). Conclusion: During the evaluation of the patients with cognitive retardation, nutritional vitamin-mineral deficiency and anemia status should be evaluated at the initial examination and the cognitive status of the patients should be re-evaluated after treatment.